Basic aspects of caring for green facades in the city of Košice - Vranayová, Zuzana; Kocúrková, Mária; Káposztásová, Daniela; Kozlovská, Mária (Frontiers in Sustainability, 2025)
IntroductionGreen façades are increasingly promoted as nature-based solutions for mitigating urban overheating, enhancing microclimate, and supporting biodiversity. However, their role in sustainable water management is still underexplored, especially in continental Central European climates with high variability in irrigation demand.MethodsThis pilot study assessed the establishment and first-year performance of a modular green façade installed at the Technical University of Koǎice, Slovakia. Six ornamental species (N = 180) were cultivated under a gravity-driven irrigation system. Irrigation events were manually recorded from November 2024 to August 2025, and plant survival and vitality were evaluated monthly in relation to meteorological data.ResultsIrrigation demand strongly correlated with air temperature, showing minimal water use during winter dormancy, gradual increase in spring, and a peak in June. The unusually cool July reduced irrigation frequency despite full vegetation coverage. Overall plant survival reached about 90%, with Carex morrowii and Hedera helix performing best, while Heuchera exhibited higher vulnerability to heat stress.DiscussionThe results highlight that Central European green façades require adaptive irrigation management but can effectively contribute to sustainable urban water strategies when resilient species are selected. These findings provide locally grounded evidence supporting the European Green Deal and the UN Sustainable Development Goals.